Anorectal and Enteric Infections in Homosexual Men - Rompalo, Anne M. (1985)
Homosexual men are at increased risk for traditional sexually transmitted anorectal infections (gonorrhea, syphilis, venereal warts, herpes and chlamydial infection) and enteric infections characterized by a low infecting inoculum (hepatitis A and B, amebiasis, giardiasis, shigellosis and campylobacteriosis). Infections account for most of the gastrointestinal symptoms in homosexual men seen at sexually transmitted disease clinics, but asymptomatic and polymicrobial infections are also common. Distinguishing three syndromes—proctitis, proctocolitis and enteritis—is clinically useful because these syndromes correlate with specific microorganisms and modes of transmission. A careful anoscopic examination, rectal Gram's stain, cultures for gonorrhea and chlamydia, VDRL and darkfield examination of suspicious lesions should be routinely done when sexually active homosexual men present with unexplained gastrointestinal symptoms. Based on the history, physical examination and initial laboratory studies, patients can usually be classified as having proctitis, proctocolitis or enteritis. This distinction facilitates selection of both confirmatory diagnostic tests and antimicrobial therapy. The effectiveness of empiric treatment regimens for asymptomatic sexual contacts or for symptomatic patients in whom microbiological tests are pending has not been studied.